Apostasy in Malaysia: an analysis on the law in Perak & Negeri Sembilan / Farah Wahida Ismail … [et al.] - Ismail, Farah Wahida; Ramlee, Nur Diana; Mohamad, Nur Syahira; Kamarul Ariffin, Nurul Farhana Atira (2014)
Apostasy is the act of denouncing one's religion to another. In Islam, apostasy is an abandonment of Islam and it is one of the most polemical issues to be discussed in Malaysia. In Malaysia, the act of apostasy resulted to legal consequences which can be subdivided under shariah matters or constitutional matters. The Lina Joy case is one of the examples of which concerns about application made by Azlina bte Jailani for a declaration order for a change of her religion from Islam to Christianity. On the other note, the religious matters such as apostasy are within the jurisdiction of the state government that has been provided in the Federal Constitution. Thus, each state has different approach in regulating laws regarding apostasy. In this project paper, we will discuss about the issue of apostasy and its legal consequences in the states of Perak and Negeri Sembilan and under the Islamic jurisprudence.